2014
DOI: 10.1373/clinchem.2013.212472
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Brain Injury in Cerebral Infections

Abstract: BACKGROUND Central nervous system (CNS) infections present a major burden of disease worldwide and are associated with high rates of mortality and morbidity. Swift diagnosis and initiation of appropriate treatment are vital to minimize the risk of poor outcome; however, tools are lacking to accurately diagnose infection, assess injury severity, and predict outcome. Biomarkers of structural neurological injury could provide valuable information in addressing some of these challenges. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 78 publications
0
17
0
4
Order By: Relevance
“…S100B has intracellular and extracellular functions, and regulates a variety of processes, including cell proliferation, activation of astrocytes during brain damage and disease, as well as promoting cancer. In humans, high levels of S100B have been associated with schizophrenia [ 44 , 45 ] and other brain-related diseases [ 46 , 47 ]. Notably, S100B was also found elevated in the brains of the minke and the bowhead whales compared to the brains of non-diving mammals (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…S100B has intracellular and extracellular functions, and regulates a variety of processes, including cell proliferation, activation of astrocytes during brain damage and disease, as well as promoting cancer. In humans, high levels of S100B have been associated with schizophrenia [ 44 , 45 ] and other brain-related diseases [ 46 , 47 ]. Notably, S100B was also found elevated in the brains of the minke and the bowhead whales compared to the brains of non-diving mammals (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…46 In a variety of neurological disorders, significant relationships exist between markers of brain injury and/or poor clinical outcome with elevated concentrations of a neuronal injury marker-neuron-specific enolase (NSE)-and two markers of astroglial injury-S100B and glial-fibrillary acidic protein (GFAP). 47 A recent pediatric TBM study showed that compared with control groups, the blood and CSF samples of suspected TBM patients contained elevated concentrations of S100B, NSE, and GFAP over the duration of treatment, which were associated with poor outcome. 46 In those who died, inflammatory markers decreased over time while combined markers of brain injury concentrations increased.…”
Section: Neuronal Injurymentioning
confidence: 99%
“…S100B secretion is elevated in the CSF in various neurodegenerative, inflammatory, and psychiatric disorders including AD, dementia, stroke, subarachnoid hemorrhage, ischemia, and brain trauma. The elevation is indicative of tissue damage or blood brain barrier disruption (Rohlwink and Figaji, 2014). In HIV infection, patients with advanced neurocognitive problems have been shown to have higher levels of CSF S100B (Pemberton and Brew, 2001).…”
Section: Csf Biomarkers For Hiv/neuroaidsmentioning
confidence: 99%